2017
DOI: 10.1177/0890117117746336
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Youth Sports Participation and Mental Health in Young Adulthood Among Finnish Males

Abstract: Despite negative outcomes related to health behavior, the findings provide support for the association between youth SP and positive mental health outcomes in adulthood among males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
(73 reference statements)
1
31
0
Order By: Relevance
“…For example, physical activity during adolescence predicts lower cardiometabolic risk in adulthood [ 55 ]. In addition, youth sport participation appears to be associated with better mental health in later life [ 56 ]. Importantly, because basketball can be modified to allow participation in various small-sided formats, it is a sport that is conducive for participation well into adulthood, thus yielding health benefits over a wide age range.…”
Section: Basketball Promotes Healthy Youthmentioning
confidence: 99%
“…For example, physical activity during adolescence predicts lower cardiometabolic risk in adulthood [ 55 ]. In addition, youth sport participation appears to be associated with better mental health in later life [ 56 ]. Importantly, because basketball can be modified to allow participation in various small-sided formats, it is a sport that is conducive for participation well into adulthood, thus yielding health benefits over a wide age range.…”
Section: Basketball Promotes Healthy Youthmentioning
confidence: 99%
“…The relation between youth's physical activity (PA) habits and adulthood health has been thoroughly examined in previous literature. For instance, Appelqvist-Schmidlechner et al [18] highlight that engaging in sports in childhood is associated with lower risk of developing mental health issues in adulthood. Ekblom-Bak et al [19] found that kids who participated in both in-and out-of-school exercise showed reduced incidence of metabolic diseases later in life, as well as higher engagement in healthy active behaviors, and better fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, according to the above, it can be considered that the RMF's competition model is structured and organized according to the characteristics of the context and the stages of training of the athlete, which contributes to the sporting and personal development of young athletes. Research shows that these aspects can have a positive influence on the mental well-being of young athletes [2,6] and in the reduction of mental anxiety situations [3,21,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that sport brings benefits at the physical, emotional, social [1], and psychological levels. Furthermore, when properly planned, it can positively influence the mental well-being of young people [2] and reduce anxiety, among other things [3]. However, it is important to know that sport at early ages can have both positive and negative psychosocial effects, so the structure of the sporting context plays a very important role [4].…”
Section: Introductionmentioning
confidence: 99%